Cognitive and affect outcomes of group learning among secondary learners in Bangladesh - Hossain, Anowar; Ahmad Tarmizi, Rohani (Elsevier, 2011)
Group learning (GL) is well recognized as a successful pedagogy in mathematics education. The purpose of this research study was to compare the effects of GL and conventional learning on 2-aspect: cognitive outcome ‘mathematics achievement’ and affect outcome ‘attitudes toward mathematics’ among secondary learners in Bangladesh. Quasi-experimental design was administered for the experiment with 168 full-time students into 2-group: an experimental (EG) group (n = 84) and a control (CG) group (n = 84). EG was exposed to GL treatment while CG was taught using conventional learning method for the duration of 15-week. Data were collected using students’ mathematics achievement test and attitudes toward mathematics questionnaire. Both EG and CG were compared using independent-sample t-test. It was found that GL had significant effect on mathematics achievement [t (166) = 34.25, p < 0.05] and attitudes toward mathematics [t (166) = 49.72, p < 0.05]. The MANOVA with repeated measure was employed to determine the main and interaction effect of GL on test-time and achievement. The multivariate tests indicated a significant main effect of time, Wilks’ Lambda = 0.065, F (1, 166) = 2373.307, p = 0.000, η2 = 0.935; a significant interaction effect of GL by time, Wilks’ Lambda = 0.310, F (1, 166) = 369.802, p = 0.000, η2 = 0.690. These findings suggest that GL is more effective than conventional learning in mathematics teaching. As such GL can be effectively incorporated to improve students’ mathematics performance in secondary schools in Bangladesh.